2006
DOI: 10.1557/jmr.2006.0242
|View full text |Cite
|
Sign up to set email alerts
|

Fracture, aging, and disease in bone

Abstract: From a public health perspective, developing a detailed mechanistic understanding of the well-known increase in fracture risk of human bone with age is essential. This also represents a challenge from materials science and fracture mechanics viewpoints. Bone has a complex, hierarchical structure with characteristic features ranging from nanometer to macroscopic dimensions; it is therefore significantly more complex than most engineering materials. Nevertheless, by examining the micro-/nano-structural changes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 77 publications
2
31
0
2
Order By: Relevance
“…In human cortical bone, cross-links occur in two forms: (i) enzymatic crosslinks-as immature intrafibrillar (dehydrodihydroxynorleucine and dehydrohydroxylysinonorleucine) and mature interfibrillar (pyridinoline and pyrrole), and (ii) nonenzymatic advanced glycation end products (AGEs), such as pentosidine, that form both intra-and interfibrillar links along the collagen backbone (16). Although the level of enzymatic cross-links stabilizes around 10-15 y of age (17,18), AGEs can increase up to fivefold with age (15,18,19), which has been correlated to reduced bone toughness and fracture resistance (20)(21)(22)(23). Similarly, excessive remodeling with age increases the osteonal density in human cortical bone; this governs the degree of microcracking and in turn affects the development of crack bridges, which provide a major source of toughening at micrometer-scale levels and above (12).…”
mentioning
confidence: 99%
“…In human cortical bone, cross-links occur in two forms: (i) enzymatic crosslinks-as immature intrafibrillar (dehydrodihydroxynorleucine and dehydrohydroxylysinonorleucine) and mature interfibrillar (pyridinoline and pyrrole), and (ii) nonenzymatic advanced glycation end products (AGEs), such as pentosidine, that form both intra-and interfibrillar links along the collagen backbone (16). Although the level of enzymatic cross-links stabilizes around 10-15 y of age (17,18), AGEs can increase up to fivefold with age (15,18,19), which has been correlated to reduced bone toughness and fracture resistance (20)(21)(22)(23). Similarly, excessive remodeling with age increases the osteonal density in human cortical bone; this governs the degree of microcracking and in turn affects the development of crack bridges, which provide a major source of toughening at micrometer-scale levels and above (12).…”
mentioning
confidence: 99%
“…The length between 30 to 60 μm, about 40 microns, the average length of about 2 to 4 microns wide, length to diameter ratio between 10 to 20. [15] Figure 3 is the infrared spectrum of sample f. Seen from the image, there are several characteristic peaks. The absorption peaks at 561 cm -1, 960 cm-1 , 603 cm -1 are the PO43 -characteristics vibration peak; at 871 cm -1 is the HPO42-characteristics vibration peak; at 1450 cm -1 belongs to the characteristics infrared spectrum(type B replace) of CO32- [14]; OH -is shown by the characteristic of vibration peak at 1310 cm -1 without 3570 cm -1.…”
Section: Experiments Methodsmentioning
confidence: 99%
“…315 While a great deal of the work to date has been focussed on metals and alloys, CT analyses of crack propagation are becoming more widespread in other areas, particularly with respect to more complex structured materials including 2D and 3D composite systems, 103,291,316 self-healing systems 111,317 and crack propagation in natural materials, e.g. bone, [318][319][320] teeth, 321 wood, 268 as well as graphite, 322 which is an important structural material for the nuclear industry. Mostafavi et al 323 found from surface DIC that unstable fracture is preceded by the sub-critical propagation of surface cracks having a scale similar to the microstructure.…”
Section: Quantitative 3d Fracture Mechanicsmentioning
confidence: 99%